Penentuan Sasaran Strategis Terhadap Perspektif Balanced Scorecard dengan Integrasi Structured SWOT Approach, ISM dan ANP di BLKI Semarang - Yudha, Arcan Taurus Rendy; Puspitasari, Diana (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
This study aimed how to make strategic objectives in BLKI Semarang with Structured SWOT Approach, ISM and ANP, the result known that learning and growth perspective has the biggest weighted from three others perspecitves about 0.971, is related by BLKI Semarang to emphasize capability itself in intern organization for enhance needfull thing about industrial worker in Indonesia especially in Center Java, for three others weighted which are 0.013 for internal business process perspective and finance perspectiv, and last weighted of 0,003 for customer perspective. There are 19 strategic objectives been made, insist of 4 strategic objectives for internal bussiness process perspectives, 3 strategic objectives of finance perspectives, 4 strategic objectives for customer perspectives, and last 8 strategic objectives for learning and growth perspectives. Therefore the biggest global weighted of whole strategic objectives which is strategic objective of membangun kegiatan berbasis kompetensi yang berwawasan industri terkini from learning and growth perspective.